(untitled) (International Journal of Physiotherapy, 2016)
Background: Majority of high altitude residents have certain clinical, physiological, anatomical and biochemical changes. Pain threshold is one of the numerable changes that may occur due to chronic hypoxia. The aim of this research was to study the long term effects of high altitude exposure on pain perception among healthy volunteer subjects. Methods: This is an observational case-control study. Two groups of healthy volunteer subjects, highland group (n=242) and lowland group (n=242) in two different cities. Assessment methods used were: Pressure algometer, was measured bilaterally three times on ten body points and Situational pain scale, which is 18 items self-report questionnaire measuring the mental representation of pain intensity in imaginary painful situations. Results: pain sensitivity was lower in highlanders compared to lowlanders (p<0.0005). While the participants’ attitudes towards imaginary painful situations trough SPS showed lesser pain sensitivity in highlanders compared to lowlanders in 72% from the total scale items. Conclusion: According to the results of the current study, pressure pain threshold is higher (pain sensitivity is lower) in highlanders compared to lowlanders. And attitudes towards imaginary painful situations are lower in highland population compared to lowland population as a long-term effect of chronic hypoxia.